Absence of experimental cross-protection induced by a Trypanosoma cruzi-like strain isolated from bats Ausência de proteção cruzada experimental induzida por uma cepa Trypanosoma cruzi-like isolada de morcego - Gabriel Antonio Nogueira Nascentes; Wendell Sérgio Ferreira Meira; Eliane Lages-Silva; Luis Eduardo Ramírez (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
This study evaluated the possibility of inoculation and reinoculation with a trypanosomatid isolated from bats that is morphologically, biologically and molecularly similar to Trypanosoma cruzi, to protect against infection by virulent strains. Non-isogenic mice were divided into 24 groups that received from zero to three inoculations of Trypanosoma cruzi-like strain RM1, in the presence or absence of Freund's adjuvant, and were challenged with the VIC or JG strains of Trypanosoma cruzi. Parasitemia and survival were monitored and animals were sacrificed for histopathological analysis. Animals immunized with Trypanosoma cruzi-like strain RM1 presented decreased parasitemia, independently of the number of inoculations or the presence of adjuvant. In spite of this reduction, these animals did not present any protection against histopathological lesions. Severe eosinophilic infiltrate was observed and was correlated with the number of inoculations of Trypanosoma cruzi-like strain RM1. These findings suggest that prior inoculation with this strain did not protect against infection but, rather, aggravated the tissue inflammatory process. Este trabalho avaliou a possibilidade da inoculação e reinoculação de um tripanossomatídeo isolado de morcego, morfológica, biológica e molecularmente semelhante ao Trypanosoma cruzi, na proteção contra a infecção por cepas virulentas. Camundongos não-isogênicos foram divididos em 24 grupos, que receberam de zero a três inóculos da cepa RM1 de Trypanosoma cruzi-like, na presença ou ausência de adjuvante de Freund e desafiados com as cepas de Trypanosoma cruzi VIC ou JG. Acompanhou-se a parasitemia e a sobrevida e os camundongos foram sacrificados para análise histopatológica. Os animais imunizados com a cepa RM1 de Trypanosoma cruzi-like apresentaram redução da parasitemia, independente do número de inóculos ou presença de adjuvante. Apesar dessa redução, os animais não apresentaram proteção contra lesões histopatológicas e observaram-se intensos infiltrados eosinofílicos que foram ...